SEJARAH PERKEMBANGAN PELABUHAN KOTA DUMAI TAHUN 1980-2014 - Putriana, Pima; Ibrahim, Bedriati; Bunari, Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: A port is a location on a coast or shore containing one or more dock ships and transfer people or cargo to or from land. Port locations are selected to optimize access to land and navigable water, for commercial demand, and for shelter from wind and waves. Indonesia as an archipelago countrywould make the port has a very strategic and vital role. Indonesia has many ports one of them is Dumai City Harbor. The purpose of this research is to know the History of Port of Dumai City, Physical Development of Port and Development of Dumai City Goods Flow. the method was descriptive method, where data were collected through interviews, documentation and literature (library studies). Data analysis was done by qualitative. Time the study began after the publication of the research license until the completion of the last revision of the essay writer. The results show that Dumai City Harbor was originally established by PT.Chevron then submitted to the government to manage it until now managed by Pelindo 1 Dumai Branch. The physical development of Dumai port is divided into phase I, II is the construction of harbor dock and port facilities while stage III addition of port facilities and the development of port city flows Dumai fluctuation and this port is an international port to support the smoothness of inter island trade and between countries.keywords: Port, Development, Dumai City.